Feline coronavirus antibody titer in cerebrospinal fluid from cats with neurological signs - SOMA, Takehisa; SAITO, Namiko; KAWAGUCHI, Masato; SASAI, Kazumi (Journal of Veterinary Medical Science, 2018)
To investigate the utility of cerebrospinal fluid (CSF) anti-feline coronavirus (FCoV) antibody test for diagnosis of feline infectious peritonitis (FIP), the antibody titers were tested in CSF and sera from 271 FIP-suspected neurological cats. CSF antibody was detected in 28 cats, which were divided into 2 groups; 15 with CSF titer of 1:80 or lower and 13 with CSF titer of 1:640 or higher. In the latter group, reciprocal serum titer/reciprocal CSF titer was 8 or lower, which is extremely lower than normal range (256-2048), and FCoV RNA was detected in all of 11 CSF samples assayed by RT-PCR. Our findings indicate that CSF titer of 1:640 or higher may be served as a candidate for the index for diagnosing FIP.